2018
DOI: 10.1002/ccd.27499
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the V‐RESOLVE (Visual Estimation for Risk prEdiction of Side Branch OccLusion in Coronary Bifurcation interVEntion) score system

Abstract: The V-RESOLVE score system is a useful tool to help risk prediction for SB occlusion and decision-making in bifurcation intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
8
1
Order By: Relevance
“…The possible reasons for the sensitivity of this study are as follows. First, the patients enrolled in the study by Dou, et al presented with bifurcation lesions with a high risk of SB occlusion, defined as a V-RESOLVE score of !12 points, 28,29) and detecting the advantage of reducing SB occlusion might be easier in the active than conservative SB-P group. Second, a small subset of patients in the authors' experimental group received an elective two-stent strategy (SB RVD of !2.5 mm), which may have decreased the incidence of SB occlusion in the active SB-P group of our study, although it has been well demonstrated that the effect of reducing SB oc-CORONARY SIDE BRANCH PROTECTION STRATEGY clusion in the experimental group is driven mainly by a provisional SB stenting strategy with the JBT technique.…”
Section: Discussionmentioning
confidence: 99%
“…The possible reasons for the sensitivity of this study are as follows. First, the patients enrolled in the study by Dou, et al presented with bifurcation lesions with a high risk of SB occlusion, defined as a V-RESOLVE score of !12 points, 28,29) and detecting the advantage of reducing SB occlusion might be easier in the active than conservative SB-P group. Second, a small subset of patients in the authors' experimental group received an elective two-stent strategy (SB RVD of !2.5 mm), which may have decreased the incidence of SB occlusion in the active SB-P group of our study, although it has been well demonstrated that the effect of reducing SB oc-CORONARY SIDE BRANCH PROTECTION STRATEGY clusion in the experimental group is driven mainly by a provisional SB stenting strategy with the JBT technique.…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to expand the sample size in future studies. (3) This study only included the confounding factors of hypertension history, diabetes history, hyperlipidemia history, and smoking history. Other confounding factors that affect the occurrence of plaques were not included, which may have biased the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of interventional radiology, the geometric parameters of left coronary artery (LCA) bifurcation zone have attracted a large amount of attention because it is highly related to the complex decision-making regarding treatment and the incidence of perioperative and postoperative adverse clinical events [1][2][3]. Additionally, the geometry of the blood vessels has been proven to be one of the causes of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…The score system encompasses six independent visually assessed risk factors, four from baseline angiography (plaque distribution, diameter stenosis of bifurcation core, bifurcation angle, and MV/SB diameter ratio), and two from prestenting angiography (MV thrombolysis in myocardial infarction [TIMI] flow grade and SB diameter stenosis before MV stenting). It has been further validated that the SB occlusion rate was significantly higher in the high‐risk group stratified by the V‐RESOLVE score, than in the nonhigh‐risk group (26.18% vs. 3.48%) 11 . Unlike other bifurcations that are more distal, the LM bifurcation has several unique specificities, including larger diameter of SB and bifurcation angle, which might affect the predictive performance of the V‐RESOLVE score 9 .…”
Section: Introductionmentioning
confidence: 95%
“…It has been further validated that the SB occlusion rate was significantly higher in the high-risk group stratified by the V-RESOLVE score, than in the nonhigh-risk group (26.18% vs. 3.48%). 11 Unlike other bifurcations that are more distal, the LM bifurcation has several unique specificities, including larger diameter of SB and bifurcation angle, which might affect the predictive performance of the V-RESOLVE score. 9 Therefore, this study aimed to determine the value of the V-RESOLVE score in unprotected LM bifurcation PCI.…”
mentioning
confidence: 99%